The Cost of Automobile Safety and Emissions Regulation to the Consumer: Some Preliminary Results - Crandall, Robert W.; Keeler, Theodore E.; Lave, Lester B. (American Economic Review, 2018)
The cost of government regulation of the automobile has been the subject of heated controversy since its inception in the mid- 1960's. Much of this controversy has centered on the costs and benefits of individual regulations, but there has been little attention paid to the overall effect of emissions and safety regulation. In this paper, we attempt to measure the effect of these regulatory policies upon the consumer cost of owning and operating an automobile.